A study on how Asia-Pacific Economic Cooperation (APEC) liberalization program affects Malaysian automotive industry / Rusnida Ramli - Ramli, Rusnida (1999)
The purpose. of this research is to evaluate the impact of APEC Liberalization Program on Ford Motor Company Malaysia (AMIM Holdings Sdn. Bhd.). AMIM Holdings is a company, which assemble Ford cars. AMIM pays more for most parts than local manufacturer pays due to the higher rate of import duties. Thus, the cost of Ford cars is higher compared to local cars, which leads to the lower demand of Ford cars. The researcher will prove that with the introduction of APEC Liberalization Program in the year 2003, the higher production costs in terms of high tariff, faced by AMIM Holdings will be reduced. APEC an initial for Asia-Pacific Economic Cooperation, is a forum for consultations and economic cooperation activities among economies located in the Asia-Pacific region